PERGESERAN PERAN MAMAK DI RUMAH GADANG DALAM NASKAH DRAMA MATRILINI KARYA WISRAN HADI: KAJIAN SOSIOLOGI SASTRA - Putera, Harya Sastra; Hamidin, Hamidin; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2017)
This study aimed to describe: (a) the character and disposition of the characters in the plays Matrilini work Wisran Hadi. (B) the character and disposition of the characters in the plays Matrilini work Wisran Hadi. This study is a qualitative study using descriptive analysis method. Data of this study is to establish a form of characterizations of Matrilini which amplifies the shifting role and impact of the shift mamak roles in the plays Matrilini work Wisran Hadi. Sources of data in this study was 5 Drama: Contest Winners Jakarta Arts Council in 2003. Data collected by reading the plays Matrilini works Wisran Hadi, then inventarization of the data. Mechanical validating data by conducting detailed description techniques, and techniques of analyzing the data, inventory the data, interpret the data and draw conclusions and write a report. Based on the results of the study, concluded the following. First, the figures showed Mamak oriented attitude towards money and so recognize it as a mamak notch. Second, the impact of the shifting role in the longhouse mamak scripted drama is the impact on self Matrilini mamak and the extended family, such as the nephew and siblings.Â Keywords: Wisran Hadi, Plays, Niniak-mamak